Isolation, Screening and Characterization of HyaluronidaseProducing Bacteria: Hyaluronidase producing bacteria - Sabuj Sahoo; Satyaranjan Mishra; Sashi Kanta Patel; Prasana KumarPanda; Anindita Nayak; Sashi Kanta Dash; Poluri Ellaiah (Iranian Journal of Pharmaceutical Sciences, 2009)
Hyaluronidase has a panoramic use in biotechnology processes and therapy due to its therapeutic, pathophysiological, physiological and biological importance.Since much of the preparations of hyaluronidases are from animal source (bovine and ovine testicular sources) with limited sources of microbial origin, that prompted the authors to screen and isolate a new promising bacterial strain with higher yield followed by its characterization employing detailed taxonomic studies. The newly isolated strain was identified based upon their micro- and macro-morphological,cultural, physiological and biochemical parameters. Twenty isolates from different pathological samples were primarily selected and further screened for their hyaluronidase producing capabilities by measuring reduction in turbidity and hydrolyzed zone of substrate hyaluronic acid. Four isolates showing marked reduction in turbidity (A600nm) and hydrolyzed zones were selected and subjected to secondary screening by shake flask fermentation. Isolate SII9 (Dental caries specimen) exhibited maximum hyaluronidase activity (117 U/ml) when compared to the reference Streptococcus mitisMTCC*2695 (106 U/ml). Aclose scrutiny of the literature revealed that the characteristics of our isolate SII9 are mostly identical to S.equisubsp. equisimiliswith few differences and thus designated as S. equi SED9.